Incidence and comparison of patient-related and technical factors for gallbladder content spillage during laparoscopic cholecystectomy - Wadhwani, Bhavya; Sharma, Munish; Patel , Gaurav (International Surgery Journal, 2026)
Background: Gallbladder perforation with spillage of bile or stones is frequently encountered during laparoscopic cholecystectomy. Although usually considered a minor intraoperative event, it may contribute to postoperative infectious complications. The relative contribution of patient-related and technical factors remains unclear. Aim of the study was to determine the incidence of gallbladder content spillage and evaluate the contribution of patient-related versus technical factors during laparoscopic cholecystectomy. Methods: A prospective observational study was conducted on 120 consecutive adult patients undergoing laparoscopic cholecystectomy at ESIC Medical College and Hospital, Basaidarapur, New Delhi between March 2024 and July 2025. Demographic variables, body mass index, ultrasonographic findings, intraoperative characteristics, and operative steps were analysed. Gallbladder content spillage was defined as intraoperative perforation with release of bile, stones, pus, mucus, or sludge. Statistical analysis was performed using Chi-square or Fisher’s exact test, with p<0.05 considered significant. Results: Gallbladder content spillage occurred in 34 patients (28.3%). The majority were females (74.2%), and 45.8% were obese. No significant association was observed between spillage and age, gender, BMI, ultrasonographic findings, or intraoperative stone characteristics. Technical factors accounted for 67.7% of spillage events compared with 32.3% attributed to patient-related factors (p=0.003). Excessive traction at the gallbladder fundus and dissection from the gallbladder fossa were the most common operative steps associated with spillage. Conclusions: Gallbladder content spillage during laparoscopic cholecystectomy occurs frequently and appears predominantly related to operative technique rather than patient characteristics. Attention to critical operative steps may reduce its incidence.